“V著也是V著”格式試析: A Study of the Structure “V 著也是 V 著”
<span data-sheets-value=""1":2,"2":"LANGUAGE NOTE | Document text in Chinese; abstract also in English."" data-sheets-userformat=""2":705,"3":"1":0,"9":0,"10":1,"12":0" data-sheets-validation-definition=""1":"1":"1":24,"2":["1":0,"5":"1":"1":0,"2":"1":2,"2":"LANGUAGE NOTE | Document text in Chinese; abstract also in English." ,"1":0,"5":"1":"1":0,"2":"1":2,"2":"LANGUAGE NOTE | Document text in Chinese only." ],"2":"1":"1":["1":4,"6":0,"1":2,"3":"TRIM","4":1,"1":3,"5":"1":2,"2":"LANGUAGE NOTE | Document text in Chinese; abstract also in English." ,"1":3,"5":"1":2,"2":"LANGUAGE NOTE | Document text in Chinese only." ,"1":2,"3":"ARRAY_ROW","4":2,"1":2,"3":"ARRAY_LITERAL","4":1,"1":2,"3":"TRIM","4":1,"1":2,"3":"EXACT","4":2,"1":2,"3":"OR","4":1,"1":2,"3":"ARRAYFORMULA","4":1,"1":1,"2":"="],"3":"R0]FTRIM:1]LSLANGUAGE NOTE | Document text in Chinese; abstract also in English.]]LSLANGUAGE NOTE | Document text in Chinese only.]]FARRAY_ROW:2]FARRAY_LITERAL:1]FTRIM:1]FEXACT:2]FOR:1]FARRAYFORMULA:1]S","3":["1":"1":0,"2":1,"3":0,"4":1,"5":1118464,"2":0],"2":"","3":0,"4":1" data-sheets-validation-id="0">LANGUAGE NOTE | Document text in Chinese; abstract also in English. <span data-sheets-value=""1":2,"2":"LANGUAGE NOTE | Document text in Chinese; abstract also in English."" data-sheets-userformat=""2":705,"3":"1":0,"9":0,"10":1,"12":0" data-sheets-validation-definition=""1":"1":"1":24,"2":["1":0,"5":"1":"1":0,"2":"1":2,"2":"LANGUAGE NOTE | Document text in Chinese; abstract also in English." ,"1":0,"5":"1":"1":0,"2":"1":2,"2":"LANGUAGE NOTE | Document text in Chinese only." ],"2":"1":"1":["1":4,"6":0,"1":2,"3":"TRIM","4":1,"1":3,"5":"1":2,"2":"LANGUAGE NOTE | Document text in Chinese; abstract also in English." ,"1":3,"5":"1":2,"2":"LANGUAGE NOTE | Document text in Chinese only." ,"1":2,"3":"ARRAY_ROW","4":2,"1":2,"3":"ARRAY_LITERAL","4":1,"1":2,"3":"TRIM","4":1,"1":2,"3":"EXACT","4":2,"1":2,"3":"OR","4":1,"1":2,"3":"ARRAYFORMULA","4":1,"1":1,"2":"="],"3":"R0]FTRIM:1]LSLANGUAGE NOTE | Document text in Chinese; abstract also in English.]]LSLANGUAGE NOTE | Document text in Chinese only.]]FARRAY_ROW:2]FARRAY_LITERAL:1]FTRIM:1]FEXACT:2]FOR:1]FARRAYFORMULA:1]S","3":["1":"1":0,"2":1,"3":0,"4":1,"5":1118464,"2":0],"2":"","3":0,"4":1" data-sheets-validation-id="0">從句法、語義、語用的三維角度出發，本文對“V著也是V著”格式進行初步考察。指出“V著也是V著”是一個緊縮結構，由於在語義上不够自足，缺乏句法獨立性，它一般要與其他小句一起構成複句。該結構構成複句的語義關係主要是兩種：因果、選擇。整個格式的語用意義是“説話人認爲某種持續行爲或狀態缺少積極性或缺乏價值，爲克服或避免這種情況，應該採取一個‘略好‘的新行爲。 Based on the three-dimensional theory, the article focuses on the syntactic & semantic & pragmatic features of the structure "V 著也是 V 著”. It argues that “V 著也是 V 著” structure is syntactically dependent and usually appears as a clause of a compound sentence. The inner semantic relationship of the compound sentence can be divided into two kinds: cause-effect and selective. The pragmatic meaning of the whole structure may be generalized as “The speaker believes one lasting state or action lacks activity or value. To change or to avoid this situation, a new action which is a little better ought to be taken”. , journal=人文中國學報, author=宛新政, year=2005, month=Aug., pages=471–484